1997
DOI: 10.1210/endo.138.1.4847
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Myeloid Growth and Differentiation by the Insulin-Like Growth Factor I Receptor1

Abstract: Flow cytometry was used to examine the expression of type I insulin-like growth factor receptors (IGF-IR) on three types of human hematopoietic cells that represent different stages of myeloid lineage development. Both HL-60 (promyeloid) and U-937 (monocytic) cells express abundant IGF-IR protein (> 79% cells positive for the IGF-IR), whereas KG-1 myeloblasts express negligible levels of IGF-IR (< 1% IGF-IR-positive cells). Exogenous IGF-I, IGF-II, and an IGF-I analog that binds poorly to IGF-binding protein-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…1,28,45 Our current findings of IGF-IR activation by des( 1-3)-IGF-I, and surface coating by IGFBP-3, support an inhibitory role for this class of IGFBP in hepatocytes. Enhanced expression of the IGF-IR may be associated with malignant transformation.…”
Section: Igf-ir-independent Pathway Of Irs-i Phosphoryhtionsupporting
confidence: 57%
“…1,28,45 Our current findings of IGF-IR activation by des( 1-3)-IGF-I, and surface coating by IGFBP-3, support an inhibitory role for this class of IGFBP in hepatocytes. Enhanced expression of the IGF-IR may be associated with malignant transformation.…”
Section: Igf-ir-independent Pathway Of Irs-i Phosphoryhtionsupporting
confidence: 57%
“…It is known that several cytokines, such as IL-6, IL-10, and TGF-β, which activate STAT3 signaling, are potent inducers of the differentiation and activation of MDSCs [97]. Interestingly, it is known that insulin/ IGF-1 signaling can control the growth of hematopoietic progenitor cells and myeloid differentiation both in Drosophila and mammalian species [98][99][100]. In Drosophila, insulin/TOR signaling regulates the size and differentiation of the hematopoietic niche [99].…”
Section: Stat3 Signaling Controls the Activity Of Immunosuppressive Cellsmentioning
confidence: 99%
“…The most powerful evidence supporting this sequestration mechanism has come from studies using the IGF-I analog des-(1-3)-IGF-I which binds IGF-I-R and stimulates DNA synthesis but does not bind IGFBP-3. In the human promyeloid cell line HL-60, adding IGFBP-3 to serum-free media inhibited cell proliferation induced by IGF-I and IGF-II but not by des- (1-3)-IGF-I [100]. Transfected Ishikawa endometrial cancer cells which overexpressed both IGF-I-R and cell membrane-bound IGFBP-3 demonstrated equal IGF-I-R binding by IGF-I and des-(1-3)-IGF-I [101].…”
Section: Igf-dependent Actions Of Igfbpsmentioning
confidence: 99%